Zika Virus: A Global Threat (Anwer Khan Modern Medical College Journal, 2017)
Zika virus is a enveloped, non-segmented, ichoshedral single-stranded, negative-sense RNA virus. It belongs to the Flaviviridae and was first isolated in 1947 from a monkey in the Zika forest, Uganda, then in mosquitoes (Aedes africanus) in the same forest in 1948 and in a human in Nigeria in 1952. Before 2007, viral circulation and a few outbreaks were documented in tropical Africa and in some areas in Southeast Asia. In 2015, Zika viral disease outbreaks were reported in Brazil of South America for the first time and it is now considered as an emerging infectious disease. This ongoing outbreak of Zika virus that began in Brazil has spread too much of South and Central America (except Canada and Chile) and the Caribbean. According to the CDC, Brazilian health authorities reported more than 404 cases of microcephaly between October 2015 and January 2016. Seventeen of those cases have a confirmed link to the Zika virus. Its natural reservoir is yet to be unknown. Transmission mainly by mosquito Aedes aegypti but it can be transmitted from human to human by blood transfusion, saliva, urine and sexual contact. Most dangerous transmission is mother to fetus through placenta. Its actual pathogenesis is not clear but the pathogenesis of the virus is hypothesized to start with an infection of dendritic cells near the site of inoculation, followed by a spread to lymph nodes and the bloodstream Other than congenital malformation (microcephaly) disease symptoms are usually mild and short-lasting self-limiting febrile illness of 4-7 days duration without severe complications. No commercial diagnostic method against Zika virus are available. The virus constitutes an important public health threat in America and also worldwide as no effective treatment or vaccine is available till now. The World Health Organization (WHO) has declared the microcephaly condition, linked to the mosquito-borne virus, a global public health emergency.Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 29-35